From Story to Script: towards a Morphology of The Peony Pavilion––a Dream/ Ghost Drama from Ming China - Zhao, Xiaohuan (Acta Orientalia Vilnensia, 2006)
University of Otago, Donghua University This article is an attempt to analyze the dramatic structure of the Mudan ting 牡丹 亭 (Peony Pavilion) as a piece of fantasy which Tang Xianzu 湯顯祖 (1550–1616) created through the utilisation of structural devices and techniques of magic tales. The particular model adopted for the textual analysis is that formulated by Vladimir Propp in Morphology of Russian Folktale. This paper starts with a comparison of Russian magic tales Propp investigated for his morphological study and Chinese zhiguai 志怪 tales which provide the prototype for the Mudan ting with a view of justifying the application of the Proppian model. The second part of this paper is devoted to a critical review of the Proppian model and method in terms of function versus non-function, tale versus move, and character versus tale / theatrical role. Further information is also given in this part as a response to challenges and criticisms this article may incur as regards the applicability of the Proppian model in inter-cultural and inter-generic studies. Part Three is a morphological analysis of the dramatic text with a focus on the main storyline revolving around the hero and heroine. In the course of textual analysis, the particular form and sequence of functions is identified, the functional scheme of each move presented, and the distribution of dramatis personae in accordance with the sphere(s) of action of characters delineated. Finally this paper concludes with a presentation of the overall dramatic structure and strategy of this play.